Genetic Polymorphisms of NLRP3 (rs4612666) and CARD8 (rs2043211) in Periodontitis and Cardiovascular Diseases - Mahendra, Jaideep (Biology (Basel), 2021)
SIMPLE SUMMARY: Researchers have been studying the relationship between gum disease and cardiac health for decades. Gum disease develops when a sticky bacterial biofilm known as plaque forms around the teeth. The bacterial plaque and its toxic byproducts sometimes migrate inside the blood vessels and get lodged in the arterial wall known as atheroma which is found to be a leading cause for heart disease. Various host products are seen to be elevated in the human body as the result of the inflammation. We focused on the relationship between the two biomolecules namely NLRP3 (rs4612666) and CARD8 (rs2043211) with gum and heart disease. Seventy patients were selected for the study and were divided into two groups. Group I consisted of patients with gum diseases only and Group 2 consisted of patients with both gum and heart disease. On analysis, certain factors such as age, cholesterol levels and poor oral health were observed to be higher in patients with both gum and heart disease. The dental plaque from the teeth and the blood drawn from these patients were collected for the testing of the above biomolecules. These were found to be higher in patients with both gum and the heart diseases. Thus, the higher levels of the above biomolecules indicated that patients with severe gum disease and poor oral health may develop a risk to develop heart problems in the future. Thus, early prevention of the oral diseases and gum ailments might reduce the risk of the future heart diseases. ABSTRACT: Background: The existing data show that inflammasomes play a role in periodontal disease pathogenesis. However, their role in the pathogenesis of periodontitis and coronary heart disease remains unclear. This study had the objective of assessing NLRP3 (rs4612666) and CARD8 (rs2043211) gene polymorphisms in dental plaque and blood of generalized chronic periodontitis (CP) patients in the presence and absence of coronary heart disease (CHD). Methods: A total of 70 subjects were divided into two groups, including CP and CP + CHD subjects. Demographic variables, periodontal, and cardiac parameters were recorded from both groups. Subgingival plaque and blood samples were obtained from both groups and were subjected to further molecular analysis for NLRP3 (rs4612666) and CARD8 (rs2043211) expression and allele change using conventional polymerase chain reaction (PCR) and gene sequencing (Sanger’s method). Results: Amongst the demographic variables, age, and monthly income were statistically significant between the two groups. Plaque index (PI), clinical attachment level (CAL), high-density lipoprotein (HDL), and low density-lipoprotein (LDL) exhibited statistically significant levels between the two groups. NLRP3 (rs4612666) and CARD8 (rs2043211) genes showed a statistically significant association of allele change (frequency) among the groups. In general, when all of the parameters were compared to the allele change of the genes, statistically significant relationships were found between the two groups. Conclusions: The present study expressed an allele change of the investigated genes which could profoundly affect the pathobiology of the two diseases under investigation.